Monitoring of single-nucleus chromatin landscape of ischemic stroke in mouse cerebral cortex across time - Ruolin Zhang; Sicheng Guo; Jie Zhou; Xiumei Lin; Ying Wang; Yiqi Wang; Muyang Li; Kaichen Zhao; Wendai Bao; Ke Shui; Chuanyu Liu; Chang Liu; et al. (Scientific Data)
Abstract Ischemic stroke constitutes a multifaceted neurological affliction that spans various cellular types. Lack of dynamic chromatin accessibility data after stroke is one of the obstacles to understanding this process. To gain insights into the variations in transcriptional regulation among various cell types subsequent to a stroke, we employed single-nucleus ATAC-seq to curate a chromatin accessibility compendium from the cerebral cortex of mice subjected to middle cerebral artery occlusion/reperfusion (MCAO/R). Tissue samples were collected at various time points including 0, 6, 12, 24 hours, and 7, 14 days post-reperfusion, in addition to Sham control group. We obtained 99,271 high-quality nuclei across nine cell types, thereby establishing the single-nucleus chromatin accessibility atlas. This atlas provides data for interpreting the regulatory mechanisms that pervade the continuum of ischemic stroke. The data presented herein constitutes a valuable resource for the comprehension of regulatory interplays within the pathology-afflicted cerebrum.